Effectiveness of Self-study Material for Teaching General Science to School Students - Das, B.C. (JOURNAL OF INDIAN EDUCATION, 2012)
In this quasi-experimental study, the traditional method adopted for teaching general science to Class IX students was compared with teaching through self-study material (SSM) for teaching general science to same students. The basic purpose of the study was to study the effectiveness of the developed SSM in comparison to the traditional teaching method for teaching general science to Class IX students. In order to accomplish these, two groups were formed, namely experimental and control. Experimental group was taught through the SSM developed by the investigator and control group was taught through the traditional method on the same curricula. Both the groups were pretested and post-tested on the three criterion variables such as criterion test, scientific reasoning, and scientific attitude. The decision regarding the comparative effectiveness of the two methods of teaching science was arrived at by comparing gain scores on the three criterion variables.